Inseminação intra-uterina por videolaparoscopia com sêmen congelado na cadela: comparação entre dois sítios de deposição - Fabiola Bono Fukushima (2008)
The aims of this study were to evaluate the technique of laparoscopic intrauterine artificial insemination (AI) in terms of intraoperative parameters and to compare spermatic distribution in the bitchs uterus after AI in two sites of seminal deposition. Twelve bitches were used in this study, all mixed-breed and weighting from six to 17kg, randomly divided in two equal groups. The animals were submitted to laparoscopic intrauterine AI in the uterine body (GI) and in the cranial portion of the left uterine horn (GII). The average time for accomplishing the AI was statistically the same in both groups. The uterine visualization and grasping were more easily performed in GI. More than one uterine puncture was needed in one animal of GI and in two of GII. Discrete hemorrhage was noticed in two animals of GI, caused by lesions in the spleen and in a blood vessel of the uterine wall; and in one of GII, due to a lesion of the broad ligament. Concerning the spermatic distribution, it occurred in the same manner in almost all the evaluated uterine segments. The number of counted spermatozoa in the evaluated segments was small compared to the insemination dose. Several factors may have influenced the obtained results. The laparoscopic AI, performed in the uterine body, is a viable technique in bitches and the dose of 300 x 106 spermatozoa allowed spermatic distribution in all the extension of uterine horns in both sites of seminal deposition